Fatigue Life Prediction under Multiaxial Variable Amplitude Loading Using a Stress Invariant Based Criterion - Vu, Quoc Huy; Vu, Dinh Quy; Le, Thi Tuyet Nhung (Old Journal, 2017)
Predicting fatigue damage for structural components subjected to variable amplitude loadings is a complex issue. In order to estimate fatigue life under those loading conditions, a multiaxial fatigue criterion must gather with a fatigue damage accumulation rule that allows capturing different damage mechanisms when they are activated. In this paper, combinations of a stress invariant based fatigue criterion with some damage accumulation rules are carried out to deal with variable amplitude loadings. An approach combining three tools, including multiaxial criterion, multiaxial S-N curves and cumulative damage rule are used in this study. Results show good correlations of fatigue life between experimental and predicted results for 1045 steel.